Studi Komparatif Kitab Hadis Karya Abdul Karim Amrullah (Haji Rasul) dan Syekh Muhammad Yunus (Tuanku Sasak) - Fitri Yenni M. Dalil; Inong Satriadi; Hafizzullah Hafizzullah (IAIN Batusangkar, 2022)
Two great Minangkabau scholars, namely Abdul Karim Amrullah (Hajj Rasul) and (Tuanku Sasak) Sheikh Muhammad Yunus who lived in the late 19th and early 20th centuries have succeeded in compiling hadith books that are used as guidelines by the community and students in madrasas. The two books compiled by Hajj Rasul are the Book of Ayqâz an-Niyâm Fima Ibtada'a min Amril Qiyâm and the book of Asy-Syir'ah, and One book of hadith was compiled by Tuanku Sasak, namely Himpoenan Hadith. These three hadith books are interesting to study because they are both written by minangkabau scholars, one of whom rejected the order and one became the teacher of the order. The method used in this study is a comparative method, by comparing the work of the two scholars. From research, it was found that the background of writing the three hadith books is the same to answer the problems of the people who developed in the Minang realm. The methods used are both maudhui methods, but in his discussion Hajj Rasul strengthened his opinion with the Quran, Ijma, Qiyas and the opinions of friends, tabiin, ulama and fiqhiyyah methods as reinforcement of his arguments. To judge the sanad hadith, these two scholars in their books use the jarh wa Ta'dil method and to assess the quality of the hadith both scholars use the tarjih method.